O direito de superfície no ordenamento jurídico brasileiro - Mazzei, Rodrigo Reis (2007)
The surface rigth is a real state figure of the right in rem, of well complex nature, with forecast in the Statue of the Cities and the Civil Code, admiting ample transferability. The studied institute possess origins in the Roman law, having the native model strong influence of the Portuguese law, even though for the historical reasons that in the past had joined them. Our legal system is beginning and it does not possess an extensive regulation on the subject, which creates a certain instability in the aplication of the institute, having foreign orders that take care of the surface right an important paper for a good interpretation of the figure. In synthesis, is about a right in rem entailed to a made concession from the proprietor to a thrid party, so that the last one can construct and/or plant in it s real state property, or, of another band, whom it alows the concessionaire to keep existing implantation already on (or even under) the base of the concession. The inclusion of such right in rem in our order can be seen as an attempt of if putting in practical the conception of social function of the proprety, sculptured in our Great Letter, making possible that immovable not used, or underutilized, they have good destination. The separation of the implantation in relation to the base of the property if operates through the suspension of the effect of the alone principle superficies solo cedit, forming themselves what it comes if calling of superficies property , in reason of the ample ones to be able that the concessionaire (=owner of the superficies property) withholds on the acession. This comprehension it finds firmed, in certain measure, the doctrine and foreign legislation, citing itself, in example, the Italian right, the Portuguese and the Argentine. It has a gamma of unfoldings and variants in the superficies relation, given to the elasticity that this admits in it sobject, being able to be simple or more complex, depending on the one that was agreed to between the parts. The surface right complains, still, examination in the horizontal plan of the property (object of the concession), aiming at the secondary setting of it s limits and the respective obligations and consequences, as also in the vertical quadrant, reason of our order not to forbid, to little of express, the concession in the subsoil and airspace. All the conclusions of the study follow a basic line: surface right is singular species of real estate right in rem, not it fitting with perfection in the habitual concepts of ius in re propria and or the constants of the triad of ius in re aliena traditionally admitted (rights of enjoyment, joy and guarantee). It s taken care of institute with vocation to give a purpose to the other person s property, having ample specter of performance, much even always acts in real estate base. In short, the institute in comment takes care of the relation that enters the proprietor of a land and another person, that they firm pact where the first one grants to as, called superficies, the right to construct (ad aedificandum) or of planting (ad plantandum) in it s property, or to keep existing construction on this, having on the ample rights of use and joy, that all deserves the attention of the specialized doctrine, therefore it can be an important instrument for the concrete application of the social function of the property